1990
DOI: 10.1007/bf03159911
|View full text |Cite
|
Sign up to set email alerts
|

Changes in synaptosomal pH and rates of oxygen radical formation induced by chlordecone

Abstract: The resting pH of 7.14 +/- 0.02 within rat cortical synaptosomes is elevated in vitro by the insecticide chlordecone, in a dose-dependent manner. Chlordecone also reduces the rate of oxygen radical formation within synaptosomes. Both of these changes can also be demonstrated following in vivo treatment of rats with chlordecone (75 mg/kg body wt). Although chlordecone increases the permeability of the plasma membrane, the increase in pH observed is unlikely to be caused by this, since in vivo administration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…In the presence of H202 + Fe2+, EDTA partially prevented the formation of DCF, and surprisingly DETAP AC enhanced DCFH oxidation, in which fluorescence intensity readings actually exceeded the upper limits of detection (Table I). There is no ready explanation for the rapid conversion of DCFH to DCF by DETAP AC in this system, although it has been reported that Fe2+-DE-TAPAC chelates may actually catalyze the formation of ethylene gas from S-methyl 2-ketothiobutyrate, phenol from benzene, and the formation of the hydroxyl spin adduct of 5,5-dimethyl-l-pyrroline N-oxide (27).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…In the presence of H202 + Fe2+, EDTA partially prevented the formation of DCF, and surprisingly DETAP AC enhanced DCFH oxidation, in which fluorescence intensity readings actually exceeded the upper limits of detection (Table I). There is no ready explanation for the rapid conversion of DCFH to DCF by DETAP AC in this system, although it has been reported that Fe2+-DE-TAPAC chelates may actually catalyze the formation of ethylene gas from S-methyl 2-ketothiobutyrate, phenol from benzene, and the formation of the hydroxyl spin adduct of 5,5-dimethyl-l-pyrroline N-oxide (27).…”
Section: Resultsmentioning
confidence: 82%
“…DCFH's lack of specificity toward reactive oxygen species is what makes it pot.entially appealing as a probe in studying toxicological phenomena. Numerous studies exist demonstrating the utility of DCFH as an index of free radical reactions that take place in the living animal following exposure to toxic chemicals (9,(27)(28)(29). Toxicology studies using DCFH have reported the following: (1) significant differences in brain DCF formation rates between vitamin E deficient mice and those provided normal diets (8); (2) significant differences in DCF formation rat.es in brain regions known to be selectively vulnerable to the neurotoxic organometals methylmercury and trimethyltin (9); (3) significant differences in brain DCF formation rates in animals pretreated with deferoxamine prior to exposure to methylmercury (30); (4) significant differences in brain DCF formation rates in animals exposed to toluene, a neurotoxic organic solvent, in contrast to no observable alt.erations in brain DCF formation in animals treated with the structurally related solvent benzene (31).…”
Section: Resuhs and Discussionmentioning
confidence: 99%